PREPARAÇÃO, CARACTERIZAÇÃO E ESTUDOS ELETROQUÍMICOS DE ELETRODOS MODIFICADOS COM DIFERENTES MONOCAMADAS AUTOORGANIZADAS - Mossanha, Rosana (2011)
In this work were studied investigated different types of modifiers for the formation of self-assembled monolayers on the gold surface. The monolayers used were formed by different structural arrangements, alkyl chains and functional groups. The thiols groups used were: 3-mercaptopropionic acid (MPA), thiolactic acid (TLA), cystamine (CYS) and 11-mercaptoundecanoic acid. The electroactivity of films of different thiols was assessed by the probe molecule, Fe(CN)63-/4-. It was possible to observe through the cyclic voltammetry technique, the formation and organization of the films, monitoring the behavior of the redox couple. The voltammograms showed a decrease in the faradaic current response with the increase of immersion time of the gold substrate in ethanolic solution of thiols, suggesting that the process of electron transfer occurs through the pinholes of the electrodes surface and tunneling. The monolayers of 3-mercaptopropionic acid (MPA) and thiolactic acid (TLA) had a better coating of the surface in immersion time of 3 hours. While the 11-mercaptopropionic acid (MUA) and cystamine (CYS) needed more time to organize the monolayer, 24 hours, because the MUA is a long chain molecule and CYS because the cleavage of S-S. The size of thiol chain influenced the surface organization, short-chain thiols tend to form monolayers with a considerable amount of defects, leading to a lower coating on the electrode surface. Indeed, the MUA that contains a high number of carbons in the chain showed a higher surface coverage, which caused loss of voltammetric response. The electrode surface roughness and the active area, calculated by the voltammetric data, showed a decrease with the formation of the monolayers on gold surface. Aiming to estimate the amount of molecules immobilized on the surface, it was calculated the superficial excess ) by voltammetric charge obtained from the reductive desorption. The obtained values were of 1.88x10-10 for Au-CYS, 5.03x10-10 to Au-MPA, 1.06x10-8 for Au-MUA and 1.35x10-10 mol.cm-2 for the Au-TLA, demonstrating an almost complete coverage of active sites on the surface. By the electrochemical impedance spectroscopy technique, it was possible to determine the kinetic parameters of the SAMs, which were consistent with those obtained by cyclic voltammetry. Analyzing the performance of sensors for dopamine determination through the VC, it was found that the SAM formed by TLA presented the most satisfactory results regarding the sensitivity and selectivity compared to the analyte DA. Studies at different scan rates for the electrodes, Au-MPA, Au-TLA and Au-CYS in the presence of the analite showed that the anodic peak current linearly increases with the square root of scan rate, indicating that the electron transfer process is controlled by diffusion of species to the electrode surface. Dopamine was quantified by CV and SWV technique, in the linear range from 1.1 to 6.6x10-7 mol L-1 with detection limits of 1,42x10-7 mol L-1 and 4,77x10-8 mol L-1, respectively. Using the technique of VOQ, TLA-Au electrode was able to distinguish between AA and DA, when present in the same solution, with a potential difference of approximately 340 mV.